The Impact of E-Learning for Christian Religious Education Seminar Courses on UPI Christian Students - Jessica Veronica; Ruth Meiraning Tyas; Tasyalizt Nainggolan (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
The Covid-19 pandemic situation has changed teaching-learning habits. Learning that is done without face-to-face or e-learning is an alternative teaching and learning activities method today. However, until now distance learning has caused various polemics, one of which is the lack of synchronization between lecturers and students. The Christian Religious Education Seminar course at the Indonesian Education University also has various impacts on students, so this research was conducted to describe the effect of online learning on students. This study uses a descriptive method with a quantitative approach. The population of this study was 121 SPAK Christian students batch 2019, with 37 samples or respondents (31%). Respondents were given a questionnaire containing seven indicators to determine the impact of e-learning. Of the seven indicators studied, only one aspect has a negative effect: reduced focus and student activity during learning activities. The lecture time coincides with the break (lunch), so student focus decreases.